B.R.E.A.S.T. Study protocol: Benefits of R-TEP EMDR protocol in Addressing diStress and Trauma in breast cancer patients - Ligorio, Livia Emma; Rossi, Alessandro Alberto; Sala, Rebecca; Pesavento, Francesca; Musco, Flavia; Mannarini, Stefania; Bollina, Roberto (Frontiers in Psychology, 2026)
BackgroundBreast cancer diagnosis and surgical treatment can be experienced as traumatic events, triggering psychological distress including anxiety, depression, and post-traumatic symptoms. The Recent Traumatic Episode Protocol (R-TEP), an early EMDR intervention, has shown efficacy in reducing psychological symptomatology following recent traumatic events.ObjectivesThis protocol describes a randomized controlled trial designed to assess the efficacy of the EMDR R-TEP protocol in primarily reducing psychological distress and post-traumatic symptoms in breast cancer patients undergoing surgery, with secondary focus on emotion regulation, hopelessness, body image and global psychological symptomatology.MethodsA prospective, longitudinal, single-blind randomized controlled trial will be conducted at the Breast Unit of ASST Rhodense (Milan, Italy). A minimum of 122 female patients, accounting for 20% attrition, with first breast cancer diagnosis scheduled for surgery will be randomized into three groups: treatment as usual (TAU), TAU plus psychoeducational intervention, and TAU plus EMDR R-TEP. Assessments will be conducted at baseline (pre-surgery), post-surgery/pre-psychological intervention, post-psychological intervention, and at 3-month follow-up. Primary outcomes include the Psychological Distress Inventory-Revised and Post-Traumatic Symptom Questionnaire.DiscussionThis protocol provides the methodological framework for generating evidence on EMDR R-TEP as an early psychological intervention for breast cancer patients.